Accept, coach, and inspire: a formula for success. Issue 3 (4th November 2014) - D. Hall-Ellis, Sylvia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Technical services librarians, catalogers and metadata specialists serve as the integral managers of comprehensive integrated systems designed to facilitate the ingestion, annotation, cataloging, storage, retrieval and distribution of organized, discoverable resources. Yet, despite the escalating costs to upgrade integrated library systems, maintain authority control for name and subject heading points of access and create original surrogate records for new library resources, technical services departments did not grow. Design/methodology/approach – The goal of sharing metadata is to reduce the local cost of its creation with minimal changes. However, research suggests that catalogers and metadata specialists review and authenticate the standards-compliant work of others, thus negating the goal of sharing and increasing the cost of building and maintaining online catalogs and discovery tools. How can a library administrator encourage the acceptance of metadata created at other information organizations and make prudent investments to support technical services functions? Findings – There are four strategies that administrators can adopt regarding these issues. Research limitations/implications – All libraries can benefit from considering the four strategies. Practical implications – First, cultivate a robust community of practice within the information organization. Second, recognize the importance of accepting standards-compliant bibliographic metadata with few modifications. Third, provide opportunities for managers to become skilled at coaching their team members. Fourth, inspire confidence. Social implications – Librarianship is a profession that an individual enters through graduate education in library and information science. As a new entrant, an individual becomes of a member of the community of practice and assumes personal responsibility for learning and mastering technical skills and competencies through experience, mentoring, professional development and continued actions (or tasks) comprising activities situated in a library or information environment. Originality/value – This is an original opinion piece.